Concurrent occurrence of Anaplasma phagocytophilum and A. marginale in bovine peripheral blood samples from southwest of Iran - BAHRAMI, S.; HAMIDINEJAT, h.; HAJI HAJIKOLAEI, MR; KAVIANIFAR, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
Anaplasma phagocytophilum and A. marginale are the most important tick-borne bacteria of veterinary and public health significance. Anaplasma phagocytophilum causes febrile disease in humans (human granulocytic-HGA) and animals. Anaplasma marginale is the aetiological agent of acute anaplasmosis, a bovine syndrome characterized by progressive hemolytic anemia associated with fever, weight loss, abortion, decreased milk production, and in some cases, death of the infected cattle. The present study was designed to investigate the prevalence of A. phagocytophilum and A. marginale in cattle from Khuzestan province, southwest of Iran. Samples were collected between March to August 2016. Farmed cattle were selected from the four geographic regions of Khuzestan province with the highest population of cattle herds: Behbahan; Dezful; Shushtar; and Ahvaz. Blood samples were collected from the jugular vein of 200 cattle Species specification was accomplished by specific Nested PCR according to amplification of the 16SrRNA gene. To identify A. marginale, semi-nested PCR product was cut with restriction endonucleases Bst 1107 I. The prevalence of the A. marginale infection (21.5 %) was higher than that of A. phagocytophilum (7.5 %), which was found in a mixed infection with A. marginale. Overall, in the present study 7.5% of cattle were infected with both A. phagocytophilum and A. marginale. Despite the healthy appearance of infected cattle, they can transmit Anaplasma to ticks and are potential continuous sources for maintaining and disseminating the organisms to the human and animals’ population. More epidemiological studies are needed to determine the vectors and reservoir animals for the Anaplasma species and to clarify the pathogenicity of A. marginale and A. phagocytophilum for humans and animals in Iran.